The CELLULOSE SYNTHASE-LIKE A and CELLULOSE SYNTHASE-LIKE C families: recent advances and future perspectives - Liepman, Aaron H.; Cavalier, David (Frontiers in Plant Science, 2012)
The CELLULOSE SYNTHASE (CESA) superfamily of proteins contains several sub-families of closely related CELLULOSE SYNTHASE-LIKE (CSL) sequences. Among these, the CSLA and CSLC families are closely related to each other and are the most evolutionarily divergent from the CESA family. Significant progress has been made with the functional characterization of CSLA and CSLC genes, which have been shown to encode enzymes with 1,4-β-glycan synthase activities involved in the biosynthesis of mannan and possibly xyloglucan backbones, respectively. This review examines recent work on the CSLA and CSLC families from evolutionary, molecular, and biochemical perspectives. We pose a series of questions, whose answers likely will provide further insight about the specific functions of members of the CSLA and CSLC families and about plant polysaccharide biosynthesis is general.